Land inequality and the origin of divergence and overtaking in the growth process: Theory and evidence - Oded Galor; Omer Moav; Dietrich Vollrath (Brown University, Department of Economics, 2003)
This research suggests that the distribution of land within and across countries affected the nature of the transition from an agrarian to an industrial economy generating diverging growth patterns across countries. Land abundance, which was beneficial in early stages of development, generated in later stages a hurdle for human capital accumulation and economic growth among countries in which land ownership was unequally distributed. The qualitative change in the role of land in the process of industrialization affected the transition to modern growth and has brought about changes in the ranking of countries in the world income distribution. Some land abundant countries that were associated with the club of the rich economies in the pre-industrial revolution era and were marked by an unequal distribution of land, were overtaken in the process of industrialization by land scarce countries and were dominated by other land abundant economies in which land distribution was rather equal. The theory focuses on the economic incentives that led landowners to resist growth enhancing educational expenditure. The basic premise of this research, regarding the negative effect of land inequality on public expenditure on education is supported empirically based on cross-state data from the High School Movement in the first half of the 20th century in the US.
Keywords: O10; O40; 330; Land Inequality; development; human capital accumulation; growth; Bodenpolitik; Öffentliche Bildungsausgaben; Industrialisierung; USA